2010
DOI: 10.1038/jes.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Bias in the estimation of exposure effects with individual- or group-based exposure assessment

Abstract: In this paper, we develop models of bias in estimates of exposure-disease associations for epidemiological studies that use group-and individual-based exposure assessments. In a study that uses a group-based exposure assessment, individuals are grouped according to shared attributes, such as job title or work area, and assigned an exposure score, usually the mean of some concentration measurements made on samples drawn from the group. We considered bias in the estimation of exposure effects in the context of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 19 publications
5
39
0
Order By: Relevance
“…Thus, the mean exposures in the 19 groups were determined with differing levels of precision. Regression coefficients will be biased in a group-based approach if group mean exposures are imprecise, as shown in theoretical studies (18,19), but the size of this bias is difficult to assess on theoretical grounds in realistic study designs as the present one, where groups differ considerably in both size and exposure variability. Empirical simulation studies are an attractive alternative to analytical statistics in such cases.…”
Section: Methodological Considerationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, the mean exposures in the 19 groups were determined with differing levels of precision. Regression coefficients will be biased in a group-based approach if group mean exposures are imprecise, as shown in theoretical studies (18,19), but the size of this bias is difficult to assess on theoretical grounds in realistic study designs as the present one, where groups differ considerably in both size and exposure variability. Empirical simulation studies are an attractive alternative to analytical statistics in such cases.…”
Section: Methodological Considerationsmentioning
confidence: 92%
“…If these properties are met, a group-based exposure assessment might lead to more stable exposure estimates compared to individual exposures measured over a limited time period, which typically suffer from considerable random measurement error (15). A regression of outcomes on group-based exposure estimates will therefore be less biased than a regression based on individualized data, in particular if groups are sufficiently large (16)(17)(18)(19). Thus, in theory, exposure-outcome associations are stronger and more correct when based on a group-based approach than when using individual exposures (20).…”
mentioning
confidence: 99%
“…pesticide usage). The use of aggregated data, isolated and/or in conjugation with individuals' indices, could be further exploited [20]. It offers a way of decreasing the misclassification Berkson error (which occur where the same approximate exposure is used for many subjects), as emphasised in numerous theoretical reports [21].…”
Section: Feasibility and Validation Of Ecological Indicators Of Contamentioning
confidence: 99%
“…The choice of modelling approaches should ideally be supported by research into the measurement errors associated with the various alternatives. Errors in grouped data are often ignored or assumed to conform to a Berkson model that does not result in bias, but recent research has shown this is not always so 11 12…”
mentioning
confidence: 99%